(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
A heat and humidity transfer model for the pilot wearing bladder anti-G garment system is developed. In the model, an 85-node human thermoregulatory model is developed for predicting pilots' thermal stresses and the coupled heat and humidity transfer equations including latent heat sorption/release of the Phase Change Materials (PCM) are utilized for the garment. Meanwhile, the garment inner boundary conditions are treated by considering the bladder effects. Also, the model is validated by comparing the simulation with experimental results. After the validation, water vapour concentration and temperature at different parts of garment and evaporation heat loss, dry heat loss and skin temperature at different parts of body are predicted and compared to study the influences of bladder. Otherwise sweat rate, sweat accumulation, mean skin temperature and comprehensive index of thermal stress under garments with different volumetric fractions of PCM are also predicted and compared to study the influences of PCM. The conclusion shows that bladders will produce more heat stress on wearers and PCM can improve the thermal performance of the bladder anti-G garment.